Educational design in six steps a strategic and practical scaffold - Harpaz, Yoram (Routledge, an imprint of the Taylor & Francis, 2020)
"The conviction that the traditional educational institutions do not cohere with the values and challenges of our age has become commonplace, yet efforts of governments, organizations and individuals have yet to produce a convincing alternative framework. Educational Design in Six Steps addresses this urgent need, providing a theoretical and practical framework for redesigning and revolutionising any educational environment, across primary, secondary and tertiary education. Offering a new philosophical perspective firmly grounded in the practical, the analysis in this book is framed in terms of six steps, all designed to promote fertile dialogue and planning, so as to benefit not only the objects of our educational enterprises, but also society as a whole. The book provides an understandable typology for setting goals, customising and adapting educational environments, and aligning classroom practice with educational theory and organisational design, offering concrete examples and probing discussion questions throughout. The book is an essential guide for school leaders, administrators, postgraduate students and anyone working to create or reimagine their distinctive educational environments"--Provided by publisher.